PERSEPSI PETANI PADI KETAN TERHADAP KINERJA PENYULUH PERTANIAN DI KECAMATAN ROKAN IV KOTO - Rivaldi, Ridho; Febrinova, Rina; gunawan, ikhsan (Universitas Pasir Pengaraian, 2025)
The performance of the Agricultural Extension Agency is expected to educate and motivate farmers to increase glutinous rice farming production in Rokan IV Koto District. However, field conditions indicate a decline in production compared to the previous year. Therefore, the objectives of this study are (1) to describe the characteristics of agricultural extension officers in Rokan IV Koto District and (2) to analyze and describe farmers' perceptions of the performance of agricultural extension officers in the district. The sample size in this study consists of 30 glutinous rice farmers. The research method used is descriptive-quantitative with an interval scale analysis technique. The results show that as a facilitator, the performance of extension officers is perceived as very good, with an average score of 3.52 (83%). As a supervisor, their performance is perceived as unsatisfactory, with an average score of 1.72 (43%). As a dynamizer, their performance also falls into the